Keeping Allergen Names Clear and Defined - Chan, Sanny K.; Pomés, Anna; Hilger, Christiane; Davies, Janet M.; Mueller, Geoffrey; Kuehn, Annette; Lopata, Andreas L.; Gadermaier, Gabriele; van Hage, Marianne; Raulf, Monika; Goodman, Richard E. (Frontiers in Immunology, 2019)
The World Health Organization/International Union of Immunological Societies (WHO/IUIS) Allergen Nomenclature Sub-Committee was established in 1986 by leading allergists to standardize names given to proteins that cause IgE-mediated reactions in humans. The Sub-Committee’s objective is to assign unique names to allergens based on a critical analysis of confidentially submitted biochemical and clinical data from researchers, often prior to publication to preserve consistency. The Sub-Committee maintains and revises the database as the understanding of allergens evolves. This report summarizes recent developments that led to updates in classification of cockroach group 1 and 5 allergens to animal as well as environmental and occupational allergens. Interestingly, routes, doses and frequency of exposure often affects allergenicity as does the biochemical properties of the proteins and similarity to self and other proteins. Information required by the Sub-Committee now is more extensive than previously as technology has improved. Identification of new allergens requires identification of the amino acid sequence and physical characteristics of the protein as well as demonstration of IgE binding from subjects verified by described clinical histories, proof of the presence of the protein in relevant exposure substances, and demonstration of biological activity (skin prick tests, activation of basophils or mast cells). Names are assigned based on taxonomy with the abbreviation of genus and species and assignment of a number, which reflects the priority of discovery, but more often now, the relationships with homologous proteins in related species.